On the Logic of Conspiracy. Theories and the Soros Myth - Valentina Pisanty (Ocula)
Against the backdrop of the general logic and rhetoric of conspiracy theories, an analysis of the Soros Myth will provide some additional perspective to the question of what makes such constructions attractive to the eyes of their followers. On the one hand, the appeal of conspiracy theories - especially in times of economic, social and political crisis - depends on the fact that, as they oversimplify reality, they make it more manageable from a cognitive and narrative point of view. On the other, they exploit the deep contradictions that run through the liberal-democratic post-1989 European narrative, according to which equality and social justice may be brought about by enlightened elites. Through the well-laid plans of ultranationalist political consultants in the years 2000, the traditional antisemitic archive from which the Soros myth draws most of its tropes has been instrumentally hybridized with a legitimate widespread concern for the erosion of ordinary citizens' agency in 21st century politics. Hence the most hackneyed commonplaces of historical antisemitism have been passed off as the struggle against the Establishment.